Analysis of regional government financial performance in central Sulawesi Province in 2019 - Dewi Salmita (Enrichment : Journal of Management, 2023)
This study aims to determine the financial performance of local governments in Central Sulawesi Province in 2019 through financial ratios. The population of this study is 13 local governments consisting of 1 City Regional Government, and 12 Regency Regional Governments. This study uses a descriptive research method with a quantitative approach. The data used is secondary data in the form of audited financial reports. The data was analyzed using financial ratios. The results of the study show that the level of regional financial independence of the Regional Government in Central Sulawesi Province in 2019 is around an average ratio of 9.92%. The lowest level of independence occurs in Banggai Islands Regency and the highest level of independence occurs in Morowali Regency. The level of effectiveness ranges from an average ratio of 96.17%. The lowest level of effectiveness occurred in Morowali Regency and while the highest level of effectiveness occurred in Palu City. The efficiency level ranges from an average ratio of 82.38%. The lowest level of efficiency occurs in Banggai Laut Regency and the highest level of efficiency occurs in Sigi Regency. In the compatibility ratio of Regional Governments in Central Sulawesi Province, the average allocation for operational expenditure is 74.5% and the allocation for capital expenditure is 25.5% with Banggai Regency as the area that prioritizes operating expenditure the most. The growth rate is around an average ratio of 13%. The highest PAD growth rate is in Banggai Islands Regency and the lowest PAD growth rate occurs in the Regional Government of North Morowali Regency.